Respuestas
Respuesta dada por:
2
X² + 2X + 32 = 0 (Ecuacion de segundo grado)
Donde: a = 1; b = 2; c = 32
![X=\frac{-b\pm \sqrt{b^2-4ac}}{2a} X=\frac{-b\pm \sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-b%5Cpm+%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
![X=\frac{-2\pm \sqrt{(2)^2-4(1)(32)}}{2(1)} X=\frac{-2\pm \sqrt{(2)^2-4(1)(32)}}{2(1)}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-2%5Cpm+%5Csqrt%7B%282%29%5E2-4%281%29%2832%29%7D%7D%7B2%281%29%7D)
![X=\frac{-2\pm \sqrt{4-128}}{2} X=\frac{-2\pm \sqrt{4-128}}{2}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-2%5Cpm+%5Csqrt%7B4-128%7D%7D%7B2%7D)
![X=\frac{-2\pm \sqrt{-124}}{2} X=\frac{-2\pm \sqrt{-124}}{2}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-2%5Cpm+%5Csqrt%7B-124%7D%7D%7B2%7D)
![X=\frac{-2\pm \sqrt{-(4)(31)}}{2} X=\frac{-2\pm \sqrt{-(4)(31)}}{2}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-2%5Cpm+%5Csqrt%7B-%284%29%2831%29%7D%7D%7B2%7D)
![X=\frac{-2\pm 2\sqrt{31} i}{2} X=\frac{-2\pm 2\sqrt{31} i}{2}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-2%5Cpm+2%5Csqrt%7B31%7D+i%7D%7B2%7D)
X = - 1 +/- 2√(31) i
X1 = -1 + 2√(31) i
X2 = -1 - 2√(31) i
X² + 8X + 16 = 48 + 16
X² + 8X + 16 - 48 - 16 = 0
X² + 8X - 48 = 0
Donde: a = 1; b = 8; c = -48
![X=\frac{-b\pm \sqrt{b^2-4ac}}{2a} X=\frac{-b\pm \sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-b%5Cpm+%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
![X=\frac{-8\pm \sqrt{(8)^2-4(1)(-48)}}{2(1)} X=\frac{-8\pm \sqrt{(8)^2-4(1)(-48)}}{2(1)}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-8%5Cpm+%5Csqrt%7B%288%29%5E2-4%281%29%28-48%29%7D%7D%7B2%281%29%7D)
![X=\frac{-8\pm \sqrt{64+192}}{2} X=\frac{-8\pm \sqrt{64+192}}{2}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-8%5Cpm+%5Csqrt%7B64%2B192%7D%7D%7B2%7D)
![X=\frac{-8\pm \sqrt{256}}{2} X=\frac{-8\pm \sqrt{256}}{2}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-8%5Cpm+%5Csqrt%7B256%7D%7D%7B2%7D)
![X=\frac{-8\pm \ 16}{2} X=\frac{-8\pm \ 16}{2}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-8%5Cpm+%5C+16%7D%7B2%7D)
X1 = (-8 + 16)/2 = 8/2 = 4
X1 = 4
X2 = (-8 - 16)/ = -24/2 = -12
X2 = -12
X1 = 4; X2 = -12
9X² + 18X + 17 = 0
a = 9; b = 18; c = 17
![X=\frac{-b\pm \sqrt{b^2-4ac}}{2a} X=\frac{-b\pm \sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-b%5Cpm+%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
![X=\frac{-18\pm \sqrt{(18)^2-4(9)(17)}}{2(9)} X=\frac{-18\pm \sqrt{(18)^2-4(9)(17)}}{2(9)}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-18%5Cpm+%5Csqrt%7B%2818%29%5E2-4%289%29%2817%29%7D%7D%7B2%289%29%7D)
![X=\frac{-18\pm \sqrt{324-621}}{18} X=\frac{-18\pm \sqrt{324-621}}{18}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-18%5Cpm+%5Csqrt%7B324-621%7D%7D%7B18%7D)
![X=\frac{-18\pm \sqrt{-288}}{18} X=\frac{-18\pm \sqrt{-288}}{18}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-18%5Cpm+%5Csqrt%7B-288%7D%7D%7B18%7D)
![X=\frac{-18\pm \sqrt{-(144)(2)}}{18} X=\frac{-18\pm \sqrt{-(144)(2)}}{18}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-18%5Cpm+%5Csqrt%7B-%28144%29%282%29%7D%7D%7B18%7D)
![X=\frac{-18\pm 12\sqrt{(2)}i}{18} X=\frac{-18\pm 12\sqrt{(2)}i}{18}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-18%5Cpm+12%5Csqrt%7B%282%29%7Di%7D%7B18%7D)
![X = -1\pm\frac{2\sqrt{2}}{3}i X = -1\pm\frac{2\sqrt{2}}{3}i](https://tex.z-dn.net/?f=X+%3D+-1%5Cpm%5Cfrac%7B2%5Csqrt%7B2%7D%7D%7B3%7Di)
![X1 = -1+\frac{2\sqrt{2}}{3}i X1 = -1+\frac{2\sqrt{2}}{3}i](https://tex.z-dn.net/?f=X1+%3D++-1%2B%5Cfrac%7B2%5Csqrt%7B2%7D%7D%7B3%7Di)
![X2 = -1 - \frac{2\sqrt{2}}{3}i X2 = -1 - \frac{2\sqrt{2}}{3}i](https://tex.z-dn.net/?f=X2+%3D+-1+-+%5Cfrac%7B2%5Csqrt%7B2%7D%7D%7B3%7Di)
Donde: a = 1; b = 2; c = 32
X = - 1 +/- 2√(31) i
X1 = -1 + 2√(31) i
X2 = -1 - 2√(31) i
X² + 8X + 16 = 48 + 16
X² + 8X + 16 - 48 - 16 = 0
X² + 8X - 48 = 0
Donde: a = 1; b = 8; c = -48
X1 = (-8 + 16)/2 = 8/2 = 4
X1 = 4
X2 = (-8 - 16)/ = -24/2 = -12
X2 = -12
X1 = 4; X2 = -12
9X² + 18X + 17 = 0
a = 9; b = 18; c = 17
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años